Physicochemical properties of tropical forest top soil in relation to depth in western Nepal - Gautam, B.; Chettri, M. K. (Banko Janakari, 2020)
Information on soil properties with regards to forest soil-depth are important for sustainable management of forest. The present study investigated the physicochemical properties of the top soil (0−30cm depth) in the three forests, viz. i) the Terai Shorea Forest (Bardia National Park), ii) the Evergreen Riverine Forest (Bardia National Park) and iii) the Puraina CF (Kailali district) of western Nepal. In the tropical forests of western Nepal, the soil texture is, moreover, loamy sand to sand. The soil bulk density ranged from 1.33−1.63 gm cm-3, and slightly increased with the increase in the soil-depth. The soil pH value ranged from 5.77−7.36. The soil organic carbon, total nitrogen (N), available phosphorus (P), and available potassium (K) were found to be in the ranges of 0.54−1.64%, 0.04−0.14%, 4.84−31.72 kg ha-1, and 204.35−557.44 kg ha-1, respectively, and all these values decreased with the increase in the soil-depth in both the forests of the protected area; however, this decreasing trend of the soil nutrients with the increase in the soil-depth was not observed in the Puraina CF as the values of the soil nutrients were lower within 0−10cm in the CF. The soil nutrients with all the depths were found to be the highest in the Terai Shorea Forest. The lower values of the soil nutrients in the Puraina CF were the result of resource extraction.